Numerical Evaluation of Aluminum-faced Sandwich Panels in Large Enclosure Fires - Al-Jahmany, Yarub; Al-Jarrah, Jawdat; Al-Waqfi, Mohammed S.; Rbehat, Diana S.; Al-Masadeh, Hassan A. (Engineering, Technology & Applied Science Research, 2024)
This study investigates numerically the safety level of using Aluminum Faced Sandwich Panels (AFSP) in case of fire inside large enclosures. The investigated sandwich roof panel has three layers; inner and outer-faced aluminum sheets and an insulation core (mainly composed of rigid polyurethane foam). Different solutions like adding natural and mechanical ventilation systems are proposed to improve the safety level of the building. The Fire Dynamics Simulator (FDS) code for low-speed flows is deployed for the numerical data to be generated. FDS is an open-source software provided by the National Institute of Standards and Technology (NIST). The final results demonstrate a significant safety level improvement in the presence of the natural and mechanical ventilation systems, compared to large enclosures without the proposed ventilations.